Worker Protection Standard: Decontamination Supplies - Frederick M. Fishel (EDIS)
Employers of pesticide handlers must make sure that decontamination supplies for washing off pesticides and pesticide residues are provided to handlers while they are doing handling tasks. Employers must make sure that decontamination supplies for washing off pesticide residues are provided to workers who are working in a pesticide-treated area and are doing tasks that involve contact with anything that has been treated with the pesticide, including soil, water, or surfaces of plants. This document is PI-116, one of a series of the Pesticide Information Office, UF/IFAS Extension. Original publication date April 2006.